Audit risk in a client portfolio context* - SIMUNIC, DAN A.; STEIN, MICHAEL T. (Contemporary Accounting Research, 1990)
This paper examines the portfolio problem of an auditor who controls the level of audit quantity and then combines investments in general market securities with investments in risky audits. We note that an auditor cannot simply choose audits to add to the portfolio but, rather, that a portfolio is constructed indirectly through a process of bidding against competitors. Thus, our analysis yields a bidding function that provides an estimate of the minimum fee an auditor is willing to accept to serve a potential new client, given existing investments. We develop propositions concerning the effects of various portfolio characteristics on the fee bid. Finally, we discuss the possible impact of a portfolio view of audit risk upon the structure of the auditing industry.